Essays in political economy: explaining policy outcomes - Júlio, Paulo Fernando Rodrigues Lérias (2021)
Several hot issues in political economy have very recently jumped to the frontlines of academic discussion, simultaneously steaming economic research with new topics and ideas. Some relevant examples include the role of lobbies in economy policy, the effect of gender quotas on the quality of the elected body, the welfare gains (or losses) from decentralization, and the sources and effects of delayed (or anticipated) economic adjustments. This dissertation provides a theoretical overview over these issues, with a special focus on the normative side. I present herein four essays, each dedicated to one of the aforementioned topics, through which I expect to contribute to foster further the debate on relevant policy implications in the eld. One of the most appealing and prominent discussions in economics is centered on the effects of rent-seeking on economic performance and welfare. While it is well understood that rent-seeking activities reduce the amount of real resources and effort put into productive activities, no clear consensus has emerged on whether this outcome can be outweighed by a more effcient reallocation of resources.